2023
DOI: 10.3390/horticulturae9060643
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Stability Analyses of Improved Strawberry Genotypes for Tropical Climate

Abstract: Strawberries are grown worldwide, and the fruit is known for its flavor, pleasant aroma, and the presence of important nutraceutical compounds. Under temperate conditions, the species is octaploid and presents a complex inheritance. Exploring polyploidy in varietal crosses is the main alternative to developing genotypes of high-temperature regions; thus, breeding programs must evaluate the interaction based on parameters, such as the heritability, stability, easy propagation, and adaptability to different soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Finally, Nascimento et al [14] estimated the adaptability and the temporal stability of strawberry (Fragaria ananassa), as well to select genotypes that are easy to propagate with lower cold requirements using a mixed linear model. Through this model, the authors showed the superiority of 11 genotypes that had the potential to be released as cultivars.…”
mentioning
confidence: 99%
“…Finally, Nascimento et al [14] estimated the adaptability and the temporal stability of strawberry (Fragaria ananassa), as well to select genotypes that are easy to propagate with lower cold requirements using a mixed linear model. Through this model, the authors showed the superiority of 11 genotypes that had the potential to be released as cultivars.…”
mentioning
confidence: 99%